VULNERABILIDADE MULTIDIMENSIONAL: DO DIREITO À CIDADE ÀS RELAÇÕES VIRTUAIS - Toledo, Rodrigo Alberto; Bernardes, Antonio; Gonçalves Junior, Oswaldo (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2022)
This manuscript approach the problems of vulnerability and social protection in three ways. In the first way, we will approach the question of the welfare state, the concept of poverty and its historical development. The concept of territory and planning, themes of the second way, is the common reference to understand an organizational and functional structure of the State implemented at economic, social and environmental development. The main dynamics for the propagation of public policies connected to the right to the city, are a cornerstone for understanding vulnerability and social protection. Finally, we propose to analyze a vulnerability based on contemporary studies, in particular, the virtual relationships. Ours objective is to confirm that thematic vulnerability make theoretical approaches, in connected analytical paths, which has as its core the concept of poverty, territorial planning and the political-social situation of subjects in relation to rights, in a complex web of social relations, which today they are also virtual.